(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The whole philosophy of Ayurveda is based on achieving, maintaining and promoting positive health. The equilibrium of various structural and functional units of the body named as Dosha, Dhatu, Mala, Agni and more important the mind results in health and disequilibrium causes disease. This era is of industrialization, stress during the work, dietary habits, lack of exercise and various varieties among the daily diet results into the disturbance of Agni or metabolism and ultimately leads to clinical entity known as Dyslipidemia. Dyslipidemia is not a single but a range of disorders with a variety of genetic and environmental determinants. It is a condition in which the levels of lipoproteins; that is; cholesterol, triglycerides or both are altered in plasma. A cluster of other metabolic risk factors are found with the dyslipidemia including obesity, glucose intolerance, insulin resistance and hypertension. Agni is responsible for all the metabolic activities of body. As per modern medicine the dyslipidemia is mainly because of the disturbances in the metabolism. Agni is involved in the metabolism at macro and micro circulation of body on the some way or the other. Many theories have been put forward with many new hypotheses describing this disorder in Ayurveda as well as in modern science; still there is enough scope to work out on its aetiopathology and management aspects; as in modern science its management aspect remains symptomatic with troublesome side effects. Until pathology is clear, treatment part remains difficult. Hence the management of this disease is merely insufficient in other systems of medicine and patients are continuously looking with a hope towards Ayurveda to overcome this challenge.